Rhabdovirus Infection Is Dependent on Serine/Threonine Kinase AP2-Associated Kinase 1 - Jun Luo; Yue Zhang; Yang Wang; Qing Liu; Luman Chen; Boyue Zhang; Yongwen Luo; Shile Huang; Xiaofeng Guo (Life, 2020)
Rabies virus (RABV) causes a fatal neurological disease in both humans and animals. Understanding the mechanism of RABV infection is vital for prevention and therapy of virulent rabies infection. Our previous proteomics analysis based on isobaric tags for relative and absolute quantitation to identify factors revealed that RABV infection enhanced AP-2-associated protein kinase 1 (AAK1) in N2a cells. In this study, to further confirm the role of AAK1, we showed that RABV infection increased the transcription and expression of AAK1 in N2a cells. AAK1 knockdown significantly decreased RABV infection in both N2a and BHK-21 cells. AAK1 knockout inhibited RABV infection in N2a cells. Furthermore, inhibition of AAK1 kinase activity using sunitinib decreased RABV infection. However, AAK1 overexpression did not change RABV infection in vitro. Therapeutic administration of sunitinib did not significantly improve the survival rate of mice following lethal RABV challenge. In addition, AAK1 knockdown decreased infection in N2a cells by vesicular stomatitis virus, which is another rhabdovirus. These results indicate that rhabdovirus infection is dependent on AAK1 and inhibition of AAK1 is a potential strategy for the prevention and therapy of rabies.